Diagnosis of cirrhosis in patients with chronic hepatitis C genotype 4: Role of ABCB11 genotype polymorphism and plasma bile acid levels - Besheer, Tarek; Arafa, Mona; Abd El-Maksoud, Mohamed; Elalfy, Hatem; Hasson, Amany; Zalata, Khaled; Elkashef, Wagdi; Elshahawy, Heba; Raafat, Doaa; Elemshaty, Wafaa; Elsayed, Eman; Zaghloul, Hosam; et al. (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: Chronic hepatitis C (CHC)-related mortality generally results from cirrhosis and subsequent complications. We aimed to investigate the potential role of plasma bile acid levels and ABCB11 1331T>C (V444A, rs2287622) (ATP-binding cassette subfamily B, member 11) gene polymorphism in fibrosis prediction in CHC genotype 4 patients. Materials and Methods: This case control study included 85 healthy control and the following 225 subjects: 170 adult patients infected with hepatitis C virus (HCV) and categorized into three groups according to liver biopsy; no fibrosis group (F0) (n=33), early fibrosis group (F1-F2) (n=61), and advanced fibrosis group (F3-F4) (n=76). Fasting bile acid levels, hepatitis C virus (HCV) genotyping, and ABCB11 1331T>C gene polymorphism were assessed. Results: The frequency of the variant homozygote genotype CC in advanced fibrosis was significantly higher than that in early fibrosis (48.7% vs. 36.1%) (odd ratio, OR =2.58; 95% confidence interval, CI=1.07-6.20; p=0.03). C allele was significantly represented in advanced fibrosis (65.8%) compared with that in early fibrosis (51.6%) (OR=1.80, 95% CI=1.10-2.93, p=0.01). A significant elevation of plasma bile acid levels in advanced fibrosis was observed compared with those in early fibrosis (p≤0.001). Receiver operating characteristic curve for plasma bile acid levels at cutoff value of 75.5 μmol/L had a 59% specificity and 97.4% sensitivity as a predictor of advanced hepatic fibrosis (AUROC=0.78%). Conclusion: We concluded that Egyptian patients having chronic hepatitis C genotype 4 with CC genotype of ABCB11 SNP 1331T>C and high plasma bile acid levels at cutoff value of 75.5 μmol/L were associated with advanced hepatic fibrosis. Cite this article as: Besheer T, Arafa M, Abd El-Maksoud Mohamed, et al. Diagnosis of cirrhosis in patients with chronic hepatitis C genotype 4: Role of ABCB11 genotype polymorphism and plasma bile acid levels. Turk J Gastroenterol 2018; 29: 299-307